Моделювання та оптимізація річного обороту стада великої рогатої худоби - Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila; Григоренко, Сергій Михайлович; Григоренко, Сергей Михайлович; Hryhorenko, Serhii (My University, 2021)
UK: В статті запропоновано методику моделювання та розрахунок оптимального обороту стада великої рогатої худоби (ВРХ) з урахуванням відповідних зоотехнічних та господарських вимог по: складу стада, вибракуванню худоби, переводу статево-вікових груп із молодших в старші, співвідношенню окремих груп в стаді, наявності худоби на початок року, кількості приплоду, поголів’я худоби, яке необхідно мати на кінець року. Це забезпечить подальше відтворення стада і зростання виробництва тваринницької продукції. Виконання обчислень здійснюється у середовищі електронних таблиць MS Excel. Доведено, що для прогнозування виходу продукції великої рогатої худоби доцільно використовувати оптимізаційну економіко-математичну модель обороту стада. Розроблена та реалізована на тваринницькому підприємстві методика дозволить збільшити виробництво і реалізацію продукції тваринництва. EN: The article proposes a method of modeling and calculation of the optimal turnover of cattle (cattle) taking into account the relevant zootechnical and economic requirements for: herd composition, culling of cattle, transfer of sex and age groups from younger to older, the ratio of individual groups in the herd the beginning of the year, the number of offspring, livestock that must be had at the end of the year. This will ensure further reproduction of the herd and increase livestock production. Herd turnover is understood as quantitative changes in the composition of age and sex groups of animals for a certain period (month, quarter, year). Based on the turnover of the herd, the volume of production and sale of livestock products, fodder base, the need for premises for animals, labor, mechanization and other production resources are planned. Herd turnover is calculated according to standards that depend on a number of factors. The main ones are the following: production rates of expanded reproduction of livestock and qualitative improvement of the herd; production direction of animal husbandry; biological features of certain species of animals; conditions for keeping and feeding animals; sanitary condition of the herd. A matrix of economic-mathematical model is formed for a specific livestock enterprise with certain initial data. The solution of the problem takes place in spreadsheets MS Excel, add-on «Solution Search». It is proved that it is expedient to use the optimization economic-mathematical model of herd turnover to predict the yield of cattle products. In the calculations, the value of the objective function is shown in kind, as prices for livestock products often change. The methodology developed and implemented at the livestock enterprise will increase the production and sale of livestock products. RU: В статье предложена методика моделирования и расчета оптимального оборота стада крупного рогатого скота (КРС) с учетом соответствующих зоотехнических и хозяйственных требований по: структуре стада, выбраковке скота, переводу половозрастных групп из младших в старшие, соотношению отдельных групп в стаде, наличию скота на начало года, количества приплода, поголовья скота, которое необходимо иметь на конец года. Это обеспечит дальнейшее воспроизводство стада и рост производства животноводческой продукции. Выполнение вычислений производится в среде электронных таблиц MS Excel. Доказано, что для прогнозирования выхода продукции крупного рогатого скота целесообразно использовать оптимизационную экономико-математическую модель оборота стада. Разработанная и реализуемая на животноводческом предприятии методика позволит увеличить производство и реализацию продукции животноводства.
Modeling and optimization of annual turnover of cattle herd
Моделирование и оптимизация годового оборота стада крупного рогатого скота
Keywords: моделювання; оборот; стадо; велика рогата худоба; критерій оптимальності; молоко; м'ясо; modeling; turnover; herd; cattle; optimality criterion; milk; meat; моделирование; крупный рогатый скот; критерий оптимальности; мясо